2014
DOI: 10.1021/jp511818k
|View full text |Cite
|
Sign up to set email alerts
|

UV-Induced Isomerization Dynamics of N-Methyl-2-pyridone in Solution

Abstract: The photoisomerization dynamics of N-methyl-2-pyridone (NMP) dissolved in CH3CNhave been interrogated by time-resolved electronic and vibrational absorption spectroscopy. Irradiation at 330 or 267 nm prepares NMP(S1) molecules with very different levels of vibrational excitation, which rapidly relax to low vibrational levels of the S1 state. Internal conversion with an associated time constant of 110(4) ps, leading to reformation of NMP(S0) molecules, is identified as the dominant (>90%) decay pathway.Much of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…In contrast, the 901 out-of-plane MECI is accessed by remaining on the S 1 (pp*) potential, without the need for any curve crossing. Such pp* mediated ring-opening was not implicated in any of our prior work on heterocyclic photoisomerisation reactions, 16,40 however those investigations did not include such an exhaustive search of the potential energy landscape and attendant MECIs.…”
Section: (C) Computational Resultsmentioning
confidence: 99%
“…In contrast, the 901 out-of-plane MECI is accessed by remaining on the S 1 (pp*) potential, without the need for any curve crossing. Such pp* mediated ring-opening was not implicated in any of our prior work on heterocyclic photoisomerisation reactions, 16,40 however those investigations did not include such an exhaustive search of the potential energy landscape and attendant MECIs.…”
Section: (C) Computational Resultsmentioning
confidence: 99%
“…Similar molecular structures have been studied by Murdock and co-workers, who focused on the photo-isomerization dynamics of aqueous N-methyl-2-pyridone. 41 They observed that, during the excited state decay, a considerable fraction of CDs undergo photoinitiated rearrangement and carbonization. Furthermore, they demonstrated that the photochemically formed radicals contribute to destroying the pyridone and, in turn, the effective uorescent structure.…”
Section: Density Functional Theory (Dft) Simulations Of Intermediate mentioning
confidence: 99%
“…TRIR data for the 1500–1800 and 1950–2250 cm –1 regions following excitation of 2-thiophenone at 267 nm (panels a and f), 2-furanone at 225 nm (b and g), N -methyl-2-pyridone at 330 nm (c and h), α-pyrone at 310 nm (d and i) and coumarin at 330 nm (e), all in solution in acetonitrile, along with the corresponding equilibrium structures. These data are adapted from refs , , and , and are also displayed with the time delays specified in the Supporting Information.…”
mentioning
confidence: 99%